2019
DOI: 10.2196/10904
|View full text |Cite
|
Sign up to set email alerts
|

Text Messaging to Enhance Behavioral Health Treatment Engagement Among Justice-Involved Youth: Qualitative and User Testing Study

Abstract: Background Mental health and substance use disorders are highly prevalent in justice-involved youth, yet only 8% of court-involved, nonincarcerated (CINI) youth in need of treatment receive it. Dual diagnosis (co-occurring psychiatric and substance use disorders) in justice-involved youth is highly predictive of recidivism. Identifying novel approaches, such as the use of mobile health (mHealth) technologies, to close this gap between need and receipt of behavioral health treatment for the CINI po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…We did not include messaging/texting in the review because evidence suggests effective public health approaches to child mental health intervention require consideration of multicomponent interventions (e.g., including multiple domains of mental health knowledge, skill training, and practice support in parenting/child/health-worker interventions) (3638). However, existing messaging/texting strategies tend to be used as support or enhancement strategies for interventions, and might be limited in serving as stand-alone mental health intervention strategies in multicomponent interventions (3941). Finally, many adults and parents in LMICs have low literacy (primary or less than primary school education) and do not have smartphones, which make a messaging approach challenging.…”
Section: Methodsmentioning
confidence: 99%
“…We did not include messaging/texting in the review because evidence suggests effective public health approaches to child mental health intervention require consideration of multicomponent interventions (e.g., including multiple domains of mental health knowledge, skill training, and practice support in parenting/child/health-worker interventions) (3638). However, existing messaging/texting strategies tend to be used as support or enhancement strategies for interventions, and might be limited in serving as stand-alone mental health intervention strategies in multicomponent interventions (3941). Finally, many adults and parents in LMICs have low literacy (primary or less than primary school education) and do not have smartphones, which make a messaging approach challenging.…”
Section: Methodsmentioning
confidence: 99%
“…This digital disparity is often not accounted for by stakeholders who expect the system-involved to function without additional assistance beyond their care team. Given that judicial requirements are high-stakes and that care delivery is fragmented, 41 digital technologies may mitigate barriers to fulfilling demands.…”
Section: Discussionmentioning
confidence: 99%
“…32,38,39 Further, such tools may offer specific advantages for youth in juvenile justice and/or child welfare systems. 41,42 One study found that text messaging between youth on probation and juvenile justice personnel is common, and that text messaging communication would be an accessible and feasible means of sending youth behavioral health appointment reminders. 42 Furthermore, the ability to provide services across geographic boundaries and reduce barriers associated with face-to-face help-seeking, 43,44 make mHealth an innovative and practical intervention that can also target barriers to care among young women with histories of CSE, a population with frequent systems involvement and similar risk profiles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many mHealth tools developed for mental health are utilized by the patients with a focus on treatment retention or delivering treatment such as counseling through the telephone or motivational messages [12,13] [14] [15]. In contrast, mCIDT focused on care seeking behavior and was utilized by lay health workers.…”
Section: Discussionmentioning
confidence: 99%